1996
DOI: 10.1128/aac.40.8.1941
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of bactericidal activity of clindamycin against Bacteroides fragilis via kill curve methods

Abstract: Kill curves were determined for five isolates of Bacteroides fragilis with clindamycin at concentrations equal to the MIC or to 4, 16, and 64 times the MIC. Examination of plots of log CFU per milliliter versus time revealed no association between the clindamycin concentration and the rate and extent of the bactericidal activity against B. fragilis at or below 64 times the MIC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 21 publications
0
11
1
Order By: Relevance
“…Metronidazole, cefoxitin and imipenem exhibited concentration‐ and exposure‐time‐dependent killing, whereas only static activity was observed after chloramphenicol and clindamycin. In contrast, Klepser et al recently demonstrated bactericidal activity of ˜0.2–1.0 log 10 CFU/mL over a 4‐h period, dependent on exposure time but not concentration [6]. The discrepancy between these observations and ours of no bactericidal activity may be explained by strain difference and different exposure media.…”
Section: Discussioncontrasting
confidence: 74%
“…Metronidazole, cefoxitin and imipenem exhibited concentration‐ and exposure‐time‐dependent killing, whereas only static activity was observed after chloramphenicol and clindamycin. In contrast, Klepser et al recently demonstrated bactericidal activity of ˜0.2–1.0 log 10 CFU/mL over a 4‐h period, dependent on exposure time but not concentration [6]. The discrepancy between these observations and ours of no bactericidal activity may be explained by strain difference and different exposure media.…”
Section: Discussioncontrasting
confidence: 74%
“…40 It is not active against multiresistant MRSA (mrMRSA), but MSSA and most strains of non-multiresistant MRSA (nmrMRSA) are generally clindamycin susceptible. [30][31][32] Clindamycin is essentially bacteriostatic, displays time-dependent activity at concentrations >4 times the MIC, 41 and has a modest in vitro postantibiotic effect against S. aureus. 42 Like the macrolides, it is bacteriostatic and therefore should be avoided as the sole treatment for endocarditis.…”
Section: Lincosamidesmentioning
confidence: 99%
“…therapy viable therapeutic options. However, despite our wealth of clinical experience with clindamycin, it is only recently that the pharmacodynamic properties of this agent have been adequately described (7,8,14).…”
Section: Discussionmentioning
confidence: 99%